Human rights, indian financial system, communication skills (FC-I) SYBSc - Basantani K.T., Doctore Aspi H., Deshmukh M.S. (Sheth publishers,Mumbai, 2008)
Commerce
ENGLISH
Keywords: Human rights, indian financial system, communication skills (FC-I) SYBSc; Commerce; Commerce